Ex vivo oocyte retrieval for fertility preservation in an adolescent patient with recurrent ovarian dysgerminoma: a case report and review of the literature - Addison W. Alley, M.D.; Leah J. Cooper, M.D., M.S.; Meredith A. Humphreys, M.D.; Benjamin R. Emery, M.Phil.; Kenneth I. Aston, Ph.D.; Zachary J. Kastenberg, M.D.; Matthew X. Luo, M.D.; Katherine G. Hayes, M.D.; Douglas Fair, M.D., M.S.; Casey Mehrhoff, D.O., M.S.; Joseph M. Letourneau, M.D.; Krista J. Childress, M.D. (F&S Reports)
Objective: To describe fertility preservation via ex vivo oocyte retrieval for an adolescent patient undergoing oophorectomy for recurrent ovarian dysgerminoma and to review the available literature regarding this technique. Design: Case report and literature review. Subjects: A 17-year-old female with a medical history of right ovarian dysgerminoma treated with oophorectomy 3 years prior, who presented with a retroperitoneal mass noted during surveillance. Biopsy of the mass and remaining ovary confirmed recurrent stage III ovarian dysgerminoma. The patient desired fertility preservation. Ovarian tissue cryopreservation and traditional transvaginal oocyte retrieval were contraindicated because of the ovarian malignancy. Exposure: The patient underwent controlled ovarian hyperstimulation with gonadotropins followed by laparotomy and left salpingo-oophorectomy 36 hours after ovulation trigger. An ex vivo retrieval of oocytes was performed under both direct visualization and ultrasound guidance in the operating room after excision of the ovary and isolated using a “mobile IVF” setup. Main Outcome Measure(s): Number of meiosis II oocytes cryopreserved. Results: A total of 12 meiosis II oocytes were retrieved from the ovary and were successfully cryopreserved. The patient tolerated the procedure well and has since completed chemotherapy. Conclusion: The combination of controlled ovarian hyperstimulation followed by ex vivo oocyte retrieval provides select patients with an opportunity for fertility preservation that may have otherwise faced a complete loss of fertility. In this case, the patient was able to preserve oocytes without jeopardizing her health status or delaying cancer therapy.